Evaluation of Pain Management after Surgery: An Observational Study - Regina Sierżantowicz; Jolanta Lewko; Dorota Bitiucka; Karolina Lewko; Bianka Misiak; Jerzy Robert Ładny (Medicina, 2020)
Background and Objectives: Choosing a pain management strategy is essential for improving recovery after surgery. Effective pain management reduces the stress response, facilitates mobilization, and improves the quality of the postoperative period. The aim of the study was to assess the effectiveness of pain management in patients after surgery. Materials and Methods: The study included 216 patients operated on in the following surgical wards: the Department of Cardiosurgery and the Department of General and Endocrine Surgery. Patients were hospitalized on average for 6 ± 4.5 days. Patients were randomly selected for the study using a questionnaire technique with a numerical rating scale. Results: Immediately after surgery, pre-emptive analgesia, multimodal analgesia, and analgosedation were used significantly more frequently than other methods (p < 0.001). In the subsequent postoperative days, the method of administering drugs on demand was used most often. Patients with confirmed complications during postoperative wound healing required significantly more frequent use of drugs from Steps 2 and 3 of the World Health Organization (WHO) analgesic ladder compared with patients without complications. Conclusion: The mode of patient admission for surgery significantly affected the level of pain perception. Different pain management methods were used and not every method was effective.